Social Capital and the Status Externality - Jun-ichi Itaya; Christopher Tsoukis (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates how the presence of social capital affects the externality arising from status-seeking preference as a parable for inefficient antagonistic behavior. It is assumed that the stock of social capital is accumulating through joint social interaction between rational individuals who are forward looking. Using a differential game, we show that although the presence of social capital mitigates the tendency of overconsumption over time, social capital ends up declining to zero. It is also shown that the benefits from social capital enhance the motivation of individuals to accumulate social capital thereby leading to deter overaccumulation and thus possibly improving social welfare.
Keywords: O40; Q33; 330; social capital; status externality; Markov perfect; equilibrium; differential game